2019
DOI: 10.1002/sej.1339
|View full text |Cite
|
Sign up to set email alerts
|

Shooting stars? Uncertainty in hiring entrepreneurs

Abstract: This article advances a theory to explain why a spell of entrepreneurship affects the future wages of entrepreneurs returning to the wage sector. We propose that entrepreneurship holds a low rather than a negative information value, increasing the uncertainty around a job applicant's future productivity. Employers respond to this uncertainty by discounting the offered wage. The theory predicts that uncertainty in hiring-and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 109 publications
(181 reference statements)
4
24
0
Order By: Relevance
“…the 2-repeat, 4-repeat, and 7-repeat variants-exhibit differences in physiological functioning with respect to dopamine releases between synaptic clefts in the human brain. It has been identified that the 7-repeat variant of the DRD4 exon III gene show a suboptimal blunted response to elevated dopamine levels relative to the ancestral 4-repeat and economically-relevant phenotypes at the level of individuals, such as financial risk-taking (Dreber et al, 2009;Kuhnen and Chiao, 2009) or creativity (Mayseless et al, 2013), thereby validating our inquiry into the link between DRD4 exon III and entrepreneurial activities, which require significant levels of novelty, tolerance to risks and creativity to succeed in today's highly competitive markets (Bruton et al, 2013;Mahieu et al, 2019).…”
Section: The Genetic Base Of Entrepreneurshipmentioning
confidence: 81%
“…the 2-repeat, 4-repeat, and 7-repeat variants-exhibit differences in physiological functioning with respect to dopamine releases between synaptic clefts in the human brain. It has been identified that the 7-repeat variant of the DRD4 exon III gene show a suboptimal blunted response to elevated dopamine levels relative to the ancestral 4-repeat and economically-relevant phenotypes at the level of individuals, such as financial risk-taking (Dreber et al, 2009;Kuhnen and Chiao, 2009) or creativity (Mayseless et al, 2013), thereby validating our inquiry into the link between DRD4 exon III and entrepreneurial activities, which require significant levels of novelty, tolerance to risks and creativity to succeed in today's highly competitive markets (Bruton et al, 2013;Mahieu et al, 2019).…”
Section: The Genetic Base Of Entrepreneurshipmentioning
confidence: 81%
“…Finally, we restrict the sample to entrepreneurs who take a job with a different firm than the one they had worked for pre‐entrepreneurship. This is because the process of hiring and retaining entrepreneurs that return to the same employer is likely to be structurally different from that of entrepreneurs who take a job at a different firm (Swider, Liu, Harris, & Gardner, 2017), and thus previous work finds no wage penalty for these entrepreneurs (Mahieu et al, 2019). After imposing these sample restrictions, we retain a sample of 16,542 entrepreneurs and their matched counterparts.…”
Section: Empirical Setting and Datamentioning
confidence: 99%
“…Nevertheless, the career consequences of this type of work experience are not well understood. Recent scholarship on the short‐term labor market effects of entrepreneurial spells documents that entrepreneurs who return to paid employment earn a wage below that of their nonentrepreneurial counterparts (e.g., Baptista, Lima, & Preto, 2012; Bruce & Schuetze, 2004; Failla, Melillo, & Reichstein, 2017; Kaiser & Malchow‐Møller, 2011; Mahieu, Melillo, Reichstein, & Thompson, 2019), with only a few exceptions (Hyytinen & Rouvinen, 2008; Luzzi & Sasson, 2016). However, the significance of this wage loss for understanding the returns to entrepreneurship depends on its persistence, something we know little about.…”
Section: Introductionmentioning
confidence: 99%
“…However, comobility into entrepreneurship is not always voluntary. Often, "failed" entrepreneurs are punished by the labor market, which means that the decision to re-enter might be driven by necessity (Mahieu et al, 2019). Comobility into entrepreneurship might be an outcome of NVT members that abandon their individual or possibly collective job search and decide to re-enter into entrepreneurship instead.…”
Section: Comobility and Re-entry Into Entrepreneurshipmentioning
confidence: 99%
“…In examining the career trajectory, we identify that 7.9% of the dyads (representing 18.3% of all individuals) re-appear in organizations with former NVT members. Although comobility might occur due to perceived benefits of staying together, there are some hints that this comobility also occurs due to necessity, for example, as it might be challenging to transition into ordinary form of employment (Mahieu et al, 2019). In the analysis, we investigate in detail the determinants of NVT members' comobility.…”
mentioning
confidence: 99%